The effects of preoperative nursing visit on anxiety and hemodynamic parameters among the candidates for general surgeries - Nahid Hatami; Alice Khachian; Tahereh Alsadat Khoubbin Khoshnazar; Fereydoon Khayeri (Shahrekord University of Medical Sciences, 2021)
Background and aims: Anxiety is a major problem among the candidates for surgery. This study aimed at investigating the effects of preoperative nursing visit (PNV) on anxiety and hemodynamic parameters among the candidates for general surgeries. Methods: This quasi-experimental study was conducted in 2018 on 104 candidates for general surgeries conveniently recruited from Imam Khomeini hospital, Islamabad-e Gharb, Iran. Participants were randomly assigned to a control and an intervention group. Participants in the control group received routine car services, while participants in the intervention group received both routine care services and a 30-60-minute PNV one day before surgery. Their anxiety and hemodynamic parameters were assessed before the intervention and before surgery. Data were collected using a demographic questionnaire, a data sheet for hemodynamic parameters, and Spielberger State-Trait Anxiety Inventory, and were analyzed using the SPSS software (v. 22.0). Results: There were no significant between-group differences regarding the pretest mean values of state and trait anxiety, heart rate (HR), and systolic blood pressure (SBP) and diastolic blood pressure (DBP) (P>0.05). However, the posttest mean values of state and trait anxiety, HR, and systolic and diastolic blood pressures in the intervention group were significantly less than the control group (P<0.05). Moreover, all these mean values significantly decreased in the intervention group (P<0.05). Conclusion: PNV is effective in significantly reducing state and trait anxiety and hemodynamic parameters among the candidates for general surgeries and hence, can be used to minimize preoperative physiological and psychological problems.